2008
DOI: 10.1158/1078-0432.ccr-07-2024
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Signal Transducer and Activator of Transcription 5 Promotes Growth of Human Prostate Cancer Cells In vivo

Abstract: Purpose: Signal transducer and activator of transcription 5a/b (Stat5a/b) is the key mediator of prolactin effects in prostate cancer cells via activation of Janus-activated kinase 2. Prolactin is a locally produced growth factor in human prostate cancer. Prolactin protein expression and constitutive activation of Stat5a/b are associated with high histologic grade of clinical prostate cancer. Moreover, activation of Stat5a/b in primary prostate cancer predicts early disease recurrence. Here, we inhibited Stat5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
129
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(139 citation statements)
references
References 37 publications
10
129
0
Order By: Relevance
“…pcDNA-CMV-PrlR and pcDNA-CMV-WTStat5a were cloned into an adenoviral vector using BD Adeno-XTM Expression System 2 (BD Biosciences, Palo Alto, CA), as previously described, 38,41,44,45,61 and according to the manufacturer's protocol. Viral stocks of adPrlR, adWTStat5a, and adLacZ were expanded in large-scale cultures, purified by double cesium chloride gradient centrifugation, and titered side-by-side using standard plaque assay in QBI-293A cells.…”
Section: Adenoviral Generation and Gene Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…pcDNA-CMV-PrlR and pcDNA-CMV-WTStat5a were cloned into an adenoviral vector using BD Adeno-XTM Expression System 2 (BD Biosciences, Palo Alto, CA), as previously described, 38,41,44,45,61 and according to the manufacturer's protocol. Viral stocks of adPrlR, adWTStat5a, and adLacZ were expanded in large-scale cultures, purified by double cesium chloride gradient centrifugation, and titered side-by-side using standard plaque assay in QBI-293A cells.…”
Section: Adenoviral Generation and Gene Deliverymentioning
confidence: 99%
“…39,41,44,75 Protein concentrations of clarified cell lysates were determined by simplified Bradford method (BioRad, Hercules, CA). Stat5a, Stat5b, and E-cadherin were immunoprecipitated from whole cell lysates with 4 mL/mL anti-Stat5a or anti-Stat5b (Millipore, Billerica, MA) polyclonal antibodies or 4 mL/mL antieE-cadherin (BD Biosciences) monoclonal antibody.…”
Section: Stat5 Induces Emt and Stemness In Pcmentioning
confidence: 99%
“…The signal transducer and activator of transcription (Stat5) signaling cascade is known to play a pivotal role in the progression of PCa (20)(21)(22)(23). Stat5 expression in human PCa tissue correlates with high histological grades of PCa and predicts early disease recurrence after initial treatment with radical prostatectomy (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Stat5a is involved in the maintenance of prostate epithelial structures whereas Stat5b mediates cell growth (21,27). In vitro, Stat5 promotes PCa progression by increasing the expression levels of cyclin D1 and Bcl-xL (23) and transcriptional activity of the androgen receptor (AR; ref. 26).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence reveals that inhibition of STAT5 affects biological behavior of cancer cells. Studies in vitro and in vivo have shown that STAT5a and STAT5b differentially regulate the motility and migration of human mammary carcinoma cells (20,21), and inhibition of Stat5a/b by antisense oligonucleotides, RNA interference, or adenoviral expression of dominant-negative Stat5a/b can induce cell death of human prostate cancer cells (22).…”
Section: Discussionmentioning
confidence: 99%